Design and Development of a Low Cost Personal Computer Based ECG Monitor - Rabbani, K Siddique-e; Abir, A Raihan; Bodiuzzaman, AKM (Bangladesh Journal of Medical Physics, 2013)
ECG equipment is vital for diagnosis of cardiac problems. However, such equipment come from the rich Western countries at a huge cost in both procurement and maintenance, and therefore cannot offer services to a large population in the Third World countries. The only solution is to design and develop such equipment in individual countries by developing local expertise. With three decades of experience, the Dhaka University group has taken a step towards developing prototypes of ECG equipment for dissemination to the healthcare service providers. This paper presents the detailed design of an PC based ECG equipment where optimized choice of components and of the design have been made keeping the cost and maintenance in view, but not sacrificing the quality, and incorporating necessary safety features to protect the patient from known hazards. Both the hardware and the software have been developed locally and are detailed in this paper. Outputs obtained from human subjects are shown which are of reasonable good quality, and have been verified using standard ECG equipment. The PC based ECG system will allow digital post processing of signals for improved diagnosis through software. Besides, this can also become part of a nationwide telemedicine system. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14701 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 115-125